The Foundations of Social Partnership. (29th September 2015) - Behrens, Martin; Helfen, Markus
Abstract: 'Social partnership' between capital and labour is a distinctive characteristic of German industrial relations. Based on a survey of 142 German employers' associations, we investigate differences in their support for partnership with unions. We find that organizational characteristics (e.g. membership density) as well as positive experiences with their union counterparts explain why employers' associations adhere to the norms of social partnership. Building on an analysis that combines political and organizational institutionalism, we find that the positive evaluation of social partnership held by employers is associated with their positive experiences in more recent interactions with unions in collective bargaining, a more encompassing definition of an association's policy domain and a long‐term history of mutual collaboration.